Solvent Effects on Phytochemical Screening Test of Red Lemongrass (Cymbopogon nardus (L.) Rendl.) Extract and its Potential as Antidiabetic Agent - Novitasari, Putri Rachma; Nuraisyah, Fatma; Prihatmadi, Farhan Adyaqsa; Nugroho, Agung Dwi; Yudhana, Anton; Akbar, Son Ali (Integrated Research and Testing Laboratory (LPPT) Universitas Gadjah Mada, 2023)
Phytochemical screening is a preliminary stage in phytochemical research which aims to provide an overview of class compounds contained in the plants. The solvents used in this study consisted of distillated water, methanol, and n-hexane solvent. The purpose of this study was to determine the secondary metabolites in Red Lemongrass (Cymbopogon nardus (L.) Rendl.) extract using different three solvents. Red Lemongrass extract was prepared by maceration method using distillated water, methanol, and n-hexane (10 gram: 100 mL) as solvents. Results of the extract were subjected to a phytochemical screening test consisting of flavonoids, alkaloids, saponins, tannins, and triterpenoids. The results of phytochemical screening showed that alkaloids, flavonoids, triterpenoids, and saponins were drawn attracted to the distillated water solvent. Meanwhile flavonoids and triterpenoids were drawn to methanol solvents. In addition, triterpenoids were drawn to n-hexane solvents. The best solvent on maceration results will be used as a reference for testing the ability of the extract as an antidiabetic agent.